Electrical behavior of n-GaAs Schottky nanowire in wide temperature range for different contacts - Souad Benykrelef; Sedik Mansouri; Hicham Helal; Abdelaziz Rabehi; Abdelaziz Joti; Zineb Benamara (The Journal of Engineering and Exact Sciences)
This research aims to study the impact of metal work function ?m on the I–V characteristics of a n-GaAs Schottky nanowire structure, using 3D Silvaco-Atlas software. The electrical characteristics have been performed in a wide temperature range of 300-550K. This allows us to study and discuss the influence of temperature and the metal work function ?m on the performance of our proposed device. The results show a great dependence between ?m and the electrical parameters. A decrease in current is observed with increasing ?m, as well as an increase in barrier height with increasing ?m and a decrease with increasing temperature.